Use of Anthocyanin Profiles When Differentiating Individual Varietal Wines and Terroirs - Kumšta, Michal; Pavloušek, Pavel; Kárník, Pavel (Food technology and biotechnology, 2014)
In recent years, the importance of wine authenticity specification has significantly influenced the world wine market. Nowadays, the importance of terroir is emphasised worldwide. Also in European countries, where varietal wines are produced predominantly, the wine authenticity is given an increasing attention. Anthocyanin pigments represent an important group of phenolic substances that are used for the evaluation of wine authenticity. In this study, altogether 17 varietal red wines originating from the village Dolní Kounice (wine-growing region Moravia, Czech Republic) are evaluated. The evaluation involved three varieties, viz. Blaufränkisch (Lemberger), Saint Laurent and Blauer Portugieser as well as three terroirs named Karlov, Šibeniční vrch and Na Nivách. Anthocyanin pigments in varietal red wines were estimated by means of the HPLC method. Thanks to the application of chemometric methods, it was possible to determine the grapevine variety and to classify red wines on the basis of delphinidin-3-O-glucoside (DpGl), malvidin-3-O-glucoside (MvGl) and delphinidin-3-O-acetylglucoside (DpGlAc) content. The terroir was discriminated on the basis of DpGl, MvGl and delphinidin-3-O-p-coumarylglucoside (DpGlCm) content.
Keywords: anthocyanin; terroir; HPLC; wine; grapevine varieties; authenticity